Analisis Perhitungan Recommended Weight Limit dan Lifting Index Pada Bagian Consumer Packing (CP), PT. Bogasari - Sari, Santika; meriyanti, meriyanti; nurfajriah, nurfajriah (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic), 2021)
In various industrial companies, especially the food industry, there are still activities that are carried out manually in handling the  process loading and unloading of goods, one of which is PT. Bogasari. PT. Bogasari is a flour company spread across Indonesia with several brands produced including KB (Kunci Biru) , CK (Cakra Kembar), LM (Red badge) , and SB (Blue Triangle). In the Consumer Packing section, which is a flour packaging place, there are still activities that are carried out manually, namely at the loading and unloading stages of goods from 3 work stations which can result in the risk of muscle injury to workers. This study aims to analyze the weight of the load that should be lifted by workers and to determines the effect of the weight of the load that has been lifted by the Consumer Packing workers in terms of safety and health conditions using the Recommended Weight Limit and Lifting Index methods. From calculations and analysis carried out on 3 work stations showing different LI values, namely for work station 1 with carton lifting activity of 4.78691069; work station 2 with the activity of lifting wrapping bags (tags) of 6,51384355; and work station 3 with box lifting activity of 4,99049243. So, it can be concluded that the activities carried out by workers from the 3 work stations have a risk of muscle injury because the resulting Lifting Index value is more than 3 (LI ? 3).